2015
DOI: 10.1007/s11695-015-1910-5
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Status, Body Composition, and Bone Health in Women After Bariatric Surgery at a University Hospital in Rio de Janeiro

Abstract: Elevation of parathyroid hormone, low dietary calcium intake, and vitamin D plasma insufficiency without BMD reduction occurred after RYGBP. Patients who underwent RYGBP had adequate lipid profiles but inadequate intake protein, polyunsaturated fatty acids, fiber, and iron. Vitamin D deficiency may occur in the late postoperative period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 52 publications
2
21
0
1
Order By: Relevance
“…Comparing women who did not undergo Roux-en-Y gastric bypass with a group of women matched by age, sex, and weight who did, the latter had better blood values regarding total cholesterol, low-density lipoprotein, and triglycerides but a higher mean parathyroid hormone level. These results matched with the observation of vitamin D deficiency in the later postoperative period in a prospective five-year follow-up survey [99].…”
Section: Menopause and Osteoporosissupporting
confidence: 84%
See 1 more Smart Citation
“…Comparing women who did not undergo Roux-en-Y gastric bypass with a group of women matched by age, sex, and weight who did, the latter had better blood values regarding total cholesterol, low-density lipoprotein, and triglycerides but a higher mean parathyroid hormone level. These results matched with the observation of vitamin D deficiency in the later postoperative period in a prospective five-year follow-up survey [99].…”
Section: Menopause and Osteoporosissupporting
confidence: 84%
“…While there is more evidence for increased risk of osteoporosis after Roux-en-Y gastric bypass than after sleeve gastrectomy, initial research indicates that there is no significant difference [97]. Roux-en-Y gastric bypass is suggested to be involved in impaired absorption of calcium and vitamin D. As a result, secondary hyperparathyroidism accompanied by increased degradation of bone material may occur [99]. The greatest amount of bone loss takes place within the axial skeleton, such as spine and ribs, an area that is particularly vulnerable even before bariatric surgery [97].…”
Section: Menopause and Osteoporosismentioning
confidence: 99%
“…Tables 1 and 2 provide an overview of the studies to date that have evaluated iron intake after RYGB and SG. After surgery, iron intake was mostly lower or even inadequate compared with the available estimated average requirements or dietary reference intake for healthy individuals (23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) . Postoperatively, the restricted dietary intake, increased satiety and reduced appetite contribute to the lower iron intake by means of a reduced intake of micronutrients (27) .…”
Section: Iron Intake After Bariatric Surgerymentioning
confidence: 99%
“…In the current series, despite of the low calcium consumption besides hypovitaminosis D, BS group did not present a higher median serum PTH. Nevertheless, the presence of secondary hyperparathyroidism among bariatric patients is still a matter of debate since some investigators reported normal levels of PTH (8,13,15), while others did not (14,18,19).…”
Section: Discussionmentioning
confidence: 99%
“…(19), what may be a caution against dumping (25). Inadequate calcium intake may contribute to impair bone homeostasis, due to increases in serum PTH and 1,25-dihydroxyvitamin D3 (1,25(OH) 2 D 3 ) (26), and a high sodium consumption may also compromises bone health (27,28).…”
Section: Discussionmentioning
confidence: 99%